Pengaruh Profitabilitas, Size, Leverage, Komite Audit, Komisaris Independen dan Umur Perusahaan terhadap Tax Avoidance - Novita Wahyu Triyanti; Kartika Hendra Titisari; Riana Rachmawati Dewi (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
In general, entrepreneurs always maximize profits. One way to maximize profits by avoiding paying taxes. Tax avoidance is a means of exploiting legal loopholes so that employers do not pay tax or pay tax but are very small. The purpose of this study was to determine the effect of profitability, size, leverage, audit committee, independent commissioners and company age on tax avoidance. This type of research is quantitative research. The sampling method uses a purposive sampling method, so as many as 30 property and real estate companies are listed on the Indonesian Stock Exchange (BEI) in 2016-2018. The data used in this research is secondary data. Data analysis method used is multiple regression analysis. The result of this study indicate that the variable profitability, audit committee, independent commissioner has no effect on tax avoidance. While the variable size, leverage, and age of the company affect the tax avoidance.